Out Come of Sahaf Enucleation Implants in 60 Patients - Abdul Hye, Zahid Kamal Siddiqi, Girdhari Lal (Pakistan Journal of Ophthalmology, 2008)
Purpose: To give an overview of surgical outcome of Sahaf enucleation implant in 60 patients. Material and Methods: A descriptive prospective study was done of patients visiting the department of Ophthalmology in Lahore General Hospital, Lahore from June 2003 to May 2006. PMMA Sahaf implant was used in all cases after enucleation. Results: A total number of 60 patients were included. Intraocular tumor was most important cause for enucleation. The second most common disorder was trauma. Three initial cases (5 %) had necrosis of the conjunctiva leading to exposure of implant, which needed reinforcement by autogenous fascia lata. Later all those cases who had thin Tenon’s fascia had a reinforcement by sclera or autogenous fascia lata. Conclusion: All patients had excellent cosmetic results, with out any serious side effects.